COMMUNICATION STYLES OF BEC STUDENTS TOWARDS THE USE OF SOCIAL MEDIA - Anastasia, Anastasia; Sunusi, Seny Luhriyani; Novia, Lely (Universitas Negeri Makassar, 2025)
This study aims to find out the communication styles used by BEC students on social media and the ways the communication styles used by BEC students on social media platforms affect their communication in terms of language use. This study used a qualitative descriptive research design, involving BEC students with data collection techniques using questionnaires, interviews, and content analysis observations. The results show that there are two communication styles most widely used by BEC students on social media, namely assertive and passive communication styles. This study also identified the language functions involved in each communication style, such as expressing opinions politely, listening and observing, and expressing discomfort or disagreement. BEC students need to consider the communication style that suits the situation and purpose of their communication on social media, and use language appropriately and effectively.